Assessment of the Boiling Water Reactor in Indonesia - Kusuma Dyah Poernamaningari (Fakultas Sains dan Matematika Universitas Kristen Satya Wacana, 2020)
Indonesia needs to provide a large enough source of energy for development purposes, not only to produce and distribute daily necessities, but also to build industries that improve the nation's competitiveness and the lives of the people. With so many people, Indonesia has the largest energy consumption of any country in the Southeast Asia region and is fifth in the Asia Pacific in primary energy consumption, after the countries of China, India, Japan and South Korea are expected to increasingly encourage Indonesia's energy needs in the future. In Indonesia the main energy source is the fossil fuel, a non-renewable energy source. With the large amount of energy demands in Indonesia, the use of fossil fuels as energy-generating materials is increasing, which results in the depletion of fuel. Besides that, use of fossil fuels in Indonesia produces carbon dioxide in the wild which can endanger the natural environment. From the problems that occur in Indonesia with the limitations and constraints in conventional energy sources, it has been found that the Nuclear Power Plant (NPP) is a viable alternative for providing electricity. The construction of the NPP would spur national industry development because various industries could be involved in the construction of nuclear power plants. One type of nuclear power plant, namely the Boiling Water Reactor (BWR) has already been implemented in several countries with some success and has advantages that could be applied in Indonesia. It is expected that the presence of nuclear power plants in Indonesia would reduce the use of fossil fuels and increase clean and renewable energy in Indonesia.